Development and Validation of Ferroptosis- and Immune-Related lncRNAs Signatures for Breast Infiltrating Duct and Lobular Carcinoma - Wei, Tao; Zhu, Ning; Jiang, Weihua; Xing, Xiao-Liang (Frontiers in Oncology, 2022)
Background Heterogeneity of breast cancer (BRCA) is significantly correlated with its prognosis. Target therapy for ferroptosis and immunity is a new cancer treatment option discovered in recent years. In the present study, we aimed to identify ferroptosis- and immune-related long non-coding RNAs (lncRNAs) to accurately predict the prognosis and diagnosis of patients with breast infiltrating duct and lobular carcinoma by integrated analyses. Methods The corresponding data for the patients with breast infiltrating duct and lobular carcinoma by integrated analyses were obtained from The Cancer Genome Atlas (TCGA). Analyses of univariate and multivariate Cox regressions were used to identify the suitable candidate biomarkers. Results We found that seven ferroptosis- and immune-related differentially expressed lncRNAs (FI-DELs) (AC007686.3, AC078883.1, ADAMTS9-AS1, AL035661.1, CBR3-AS1, FTX, and TMEM105) were correlated with the overall survival of patients with breast infiltrating duct and lobular carcinoma. The areas under the receiver operating characteristic (AUCs) value of the prognosis model were all over 0.6 in training, validation, and entire groups. The sensitivity and specificity of the diagnosis model was 87.84% and 97.06%, respectively. Conclusions Through a series of bioinformatics analyses, we found that the seven FI-DELs could serve as prognostic and diagnostic biomarkers for patients with breast infiltrating duct and lobular carcinoma. However, whether these seven biomarkers could be really applied to the clinic requires further investigations.